Subcutaneous emphysema after dental stain removal with airflow: a case report and anatomical review - Albert, A.; Anggraini, W.; Lestari, Widya (CRC Press, Taylor & Francis Group, 2024)
Subcutaneous emphysema occurs when air is forced under the subcutaneous soft tissue, causing fascial dissection of the affected area. Cases of subcutaneous emphysema are rare; therefore dentists are not aware of this risk during dental procedures. In this case, a 19-year old woman came to the dental clinic for the purpose of cleaning tartar and stains. The initial diagnosis was gingivitis. Scaling was performed using an ultra-sonic scaler and stain removal was performed using dental airflow method. When the operator performed airflow in the buccal area of ​​teeth #16 and 17, extra-oral facial swellings suddenly occurred and the treatment procedure was stopped immediately. The patient’s face appeared asymmetrical, swelling occurred in the cheek area extending to the orbital so that the anatomical landmarks of the right face were lost. Palpation showed crepitus, but the patient felt no pain. Based on clinical examination, the case was diagnosed as subcutaneous emphysema. The treatment given was administration of 500 mg of the intra oral antibiotic amoxicillin 3 times a day for 5 days and warm water compresses. On the 2 nd day, the face remained asymmetrical and crepitus was still present. On the 3 rd day, the patient's face was symmetrical, there was no crepitus; and on the 7 th day of examination, patient showed normal clinical appearance. In conclusion, various dental procedures using high pressure air have the potential to cause subcutaneous emphysema. The focus of treatment in this case is to avoid secondary infection by administration of antibiotics.